Comparison of Emergency Echocardiographic Results between Cardiologists and an Emergency Medicine Resident in Acute Coronary Syndrome - Rasooli, Fatemeh; Bagheri, Farideh; Sadatnaseri, Azadeh; Ashraf, Haleh; Bahreini, Maryam (Archives of Academic Emergency Medicine, 2021)
Introduction: Early detection of regional wall motion abnormality (RWMA) can be a reliable tool for rapid disposition of patients with acute coronary syndrome (ACS) in the emergency department. In this study, the diagnostic accuracy of point-of-care echocardiography performed by a trained emergency medicine resident was evaluated in comparison with board-certified cardiologists. Methods: A prospective, cross-sectional study was implemented on adult patients with ACS. A trained emergency medicine (EM) PGY-3 resident performed point-of-care echocardiography under the supervision of two cardiologists and the reports were compared with cardiologists as a reference test. Results: 100 patients with the mean age of 54.1 ± 11.5 years were recruited (65% male). Based on Thrombolysis in Myocardial Infarction (TIMI) and History, EKG, Age, Risk factors, and troponin (HEART) scores, 43.0% and 25.0% of patients were categorized as low-risk for ACS, respectively. The absolute measure of agreement between cardiologists to determine ejection fraction (EF) was 0.829 (95% CI: 0.74-0.89) based on intraclass correlation coefficient (ICC) estimation. The measurements of agreement between specialists and the EM resident based on the analysis of Kappa coefficient were 0.677 and 0.884 for RWMA and pericardial effusion, respectively. Moreover, 25 patients were in the-low risk group according to the HEART score with an agreement rate of 92% for the lack of RWMA between the EM resident and cardiologists. Conclusion: This study found acceptable agreement between the EM resident and cardiologists in assessing RWMA in different ACS risk groups. In addition, there was acceptable agreement between the EM resident and cardiologists in determining left ventricular ejection fraction (LVEF) and pericardial effusion.